Sales Force Evaluation by Local and Foreign Wholesale Companies in Singapore - Rajah V. Komaran; Tok Lee Ching (Asian Academy of Management Journal, 1997)
Sales Force Evaluation by Local and Foreign Wholesale Companies in Singapore (PDF not available)